A comprehensive revision on the use of quinoline antimalarial drugs as leishmanicidal agents - Avanzo, Romina E.; García Liñares, Guadalupe; Rodríguez, Noris; Romero, Angel H. (Frontiers in Chemistry, 2025)
Antimalarial drugs based on quinolines have been widely used as leishmanicidal agents for either cutaneous or visceral leishmaniasis models. Herein, we showed the leishmanicidal response against in vitro models of different Leishmania spp. and against in vivo models of eleven key antimalarials, including chloroquine, sitamaquine, amodiaquine, mefloquine, quinine, primaquine, hydroxychloroquine, tafenoquine, quinacrine and moxipraquine. Mechanistic studies and advances in clinical treatment are also discussed. This mini-review aims to show the state of the art in using antimalarial drugs to discover alternative therapies for leishmaniasis treatment.